STRENGTHENING DIGITAL LITERACY AS AN EFFORT TO BUILD LIBRARIAN SKILLS IN PROVIDING REFERRAL OPTIONS TO USERS - Zafirah Quroatun Uyun (JURNAL ILMU PERPUSTAKAAN (JIPER), 2022)
AbstrackThe information society era 5.0 not only requires librarians to master information literacy, but also master digital literacy considering that the rapid flow of information occurs legally and illegally in cyberspace. Digital skills require librarians and users to interact interactively through the virtual world and the real world. Unfortunately, digital skills are still the main problem for librarians in carrying out their activities as professionals. practical ways such as providing references to users by relying on individual knowledge and individual preference tendencies cause users to be confused with the minimal references available and the librarian's ideology that affects references, when in fact it is not because of the availability of reference collections that availability is problematic but rather complicated collection classification methods and services. as well as the objectivity of selecting the right reference. technology, especially in the field of communication and information, is actually used to simplify activities, not to complicate them. Problems such as complex collection and service classification methods can be solved by mastering digital skills. This research tries to provide an overview of strengthening aspects of digital literacy for librarians. by using exploratory qualitative methods, aspects of digital literacy will be described through literature review and exploration of findings in the field. This research is expected to be able to answer the problem of information disruption which causes the need for library users to be hampered.